Estratégia de manufatura e estratégia corporativa: um estudo sobre o seu alinhamento em uma montadora de veículos automotores - Tigges, Matthias Rainer (2011)
The manufacturing strategy plays a key role in supporting the corporate strategy in the business, which explains the growing interest in studying the characteristics of the manufacturing strategy and its relevant factors in organizations. Early research on manufacturing strategy began in the sixties, but it was only in the last 20 years that studies have been intensified. Based on the comprehensive content available in the literature regarding the subject, this study aims to demonstrate in what degree manufacturing strategy and corporate strategy of Volkswagen Brazil are aligned. Through interviews with seven senior executives, information was obtained to identify the stage of the role of manufacturing strategy in the company. Assessed areas were planning and product management, corporate strategy of the company, quality assurance, operations, manufacturing engineering and planning, finance and corporate strategy. This study explores the main elements that characterize the alignment between the strategies considered, like the stage of maturity in relation to practice behaviors that develop competitive advantages. The manufacturing skills such as quality, reliability, loyalty applications, flexibility, cost and innovation are valued according to each technical area, highlighting the biases of the different points of view about the relevance and priority within the corporation and its contribution to manufacturing strategy. The harmonization between manufacturing strategy and corporate strategy requires huge resources and the commitment at all levels of the company. This case study identifies the difficulties and suggests a favorable environment for the growth of the strategic alignment of firm.